2004
DOI: 10.1074/jbc.m401621200
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of HIV-1 Nef on CD4 Surface Expression and Viral Infectivity in Lymphoid Cells Are Independent of Rafts

Abstract: The HIV-1 Nef protein is a critical virulence factor that exerts multiple effects during viral replication. Nef modulates surface expression of various cellular proteins including CD4 and MHC-I, enhances viral infectivity, and affects signal transduction pathways. Nef has been shown to partially associate with rafts, where it can prime T cells for activation. The contribution of rafts during Nef-induced CD4 down-regulation and enhancement of viral replication remains poorly understood. We show here that Nef do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 95 publications
3
33
1
Order By: Relevance
“…This role has been, however, questioned, because CD4 molecules unable to associate with rafts still allow virus entry (Percherancier et al, 2003;Popik and Alce, 2004). Moreover, Sol-Foulon and coworkers proposed that the effects of Nef on CD4 downregulation and the increase in viral infectivity were independent of lipid rafts (Sol-Foulon et al, 2004). Discrepancies in methodological approaches from these authors with the reports described before could account for the observed differences on this effect of Nef.…”
Section: Nef and Virus Assemblycontrasting
confidence: 46%
“…This role has been, however, questioned, because CD4 molecules unable to associate with rafts still allow virus entry (Percherancier et al, 2003;Popik and Alce, 2004). Moreover, Sol-Foulon and coworkers proposed that the effects of Nef on CD4 downregulation and the increase in viral infectivity were independent of lipid rafts (Sol-Foulon et al, 2004). Discrepancies in methodological approaches from these authors with the reports described before could account for the observed differences on this effect of Nef.…”
Section: Nef and Virus Assemblycontrasting
confidence: 46%
“…In all experiments, a Gly-to-Ala point mutation was introduced by PCR at residue position 2 of the Nef consensus sequence; this mutation has been shown to obviate Nef-mediated major histocompatibility complex (MHC) class I down-regulation. 28 Except for residue G2, the predicted 207-residue translation product of the consensus Nef sequence is 100% identical to that of an array of synthetic overlapping peptides (OLPs) covering the 2001 B consensus Nef sequence, allowing a direct comparison of immune responses to mRNA and synthetic peptide.…”
Section: Synthetic Mrna Encoding the 2001 Clade B Consensus Nucleotidmentioning
confidence: 99%
“…In addition, various proteins fused to Vpr were shown to be efficiently incorporated into HIV-1 particles while retaining their original properties (17,32,57,93,94). Since the myristoylation of Nef is important for most of the functions of Nef investigated so far (8,82,91), we decided to fuse Vpr to the C-terminal end of Nef as depicted in Fig. 1.…”
Section: Viral Infectivity Correlates With Cellular and Viral Levels Ofmentioning
confidence: 99%